Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Keterampilan Berpikir Kritis Dan Hasil Belajar IPA Siswa Tingkat Sekolah Dasar - Sunarti; Nurlina; Maaruf (Program Studi Manajemen Pendidikan, 2023)
This study aims to analyze the learning model of Guided Inquiry on Critical Thinking Skills and learning outcomes. The type of research used in this research is quantitative research (quasi experiment). The subjects used in this study were students of class V with a total of 58 students consisting of two classes (VA and VB). The instruments used in this study were in the form of instruments, namely tests, observation sheets and documentation. Data analysis techniques were carried out, namely descriptive tests (mean, median, mode and standard deviation) and inferential tests (Normality, Homogeneity and Manova). Based on data analysis using SPSS 25, the normality test for cyan literacy and learning outcomes using Kolmogorov-Smirnov is sig > 0.05 from the pretest and posttest results of the control and experimental classes and the homogeneity test using the based mean is sig > 0.05 from the pretest and posttest results of the control and experimental classes, while the Manova test shows a significance value of 0.000. 0.000 < 0.05 then